2008
DOI: 10.1097/psy.0b013e318164f911
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Obesity Prevention Programs: How Do They Affect Eating Pathology and Other Psychological Measures?

Abstract: The existing evidence does not support the view that childhood obesity prevention programs are associated with unintended psychological harm. However, because these variables have been so poorly assessed, conclusions about the possible iatrogenic effects of these programs are premature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 41 publications
1
42
0
Order By: Relevance
“…39,40 As recently suggested, 41 obesity interventions should take these issues into account, including an evaluation whether these programmes increase the risk of unhealthy food restraint and subsequently eating disorders. We found no signs of negative effects of the intervention as measured by self-report.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 As recently suggested, 41 obesity interventions should take these issues into account, including an evaluation whether these programmes increase the risk of unhealthy food restraint and subsequently eating disorders. We found no signs of negative effects of the intervention as measured by self-report.…”
Section: Discussionmentioning
confidence: 99%
“…[19] The inconsistent findings are largely due to differences in the design of the reviews, their methods, and the quality of the primary literature (e.g., small study size, lack of blinding, short follow-up, and varied statistical analyses. [12][13][14][15][16][17][18][19][20][21][22][23][24] Pediatric obesity prevention programs caused small changes in target behaviors and no significant effect on BMI compared with control.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have provided convincing evidence that broad-based obesity prevention programs in fact decrease eating pathology [56,57], whereas another recent study indicates that decreasing competitive food offerings did not increase eating and weight concerns in students [51]. A review focused on this question concluded that childhood obesity prevention programs do not appear to have a negative impact on eating pathology [58]. The evidence to date supports the position that eating disorder and obesity prevention efforts need not be inimical, rather offer the opportunity to work toward a common goal.…”
Section: Schools As An Important Starting Pointmentioning
confidence: 99%